2013
DOI: 10.1007/s10569-013-9479-6
|View full text |Cite
|
Sign up to set email alerts
|

High precision symplectic integrators for the Solar System

Abstract: Using a Newtonian model of the Solar System with all 8 planets, we perform extensive tests on various symplectic integrators of high orders, searching for the best splitting scheme for long term studies in the Solar System. These comparisons are made in Jacobi and Heliocentric coordinates and the implementation of the algorithms is fully detailed for practical use. We conclude that high order integrators should be privileged, with a preference for the new (10, 6, 4) method of (Blanes et al, 2012).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 40 publications
0
79
0
Order By: Relevance
“…The orbits of the planets were integrated with the symplectic integrator SABA1064 of Farrés et al (2013), using a step size of 5×10 −3 yr and general relativity corrections. The fundamental frequencies of the systems are the mean motions n b and n c , and the two secular frequencies of the pericenters g 1 and g 2 (Table 6).…”
Section: Secular Couplingmentioning
confidence: 99%
“…The orbits of the planets were integrated with the symplectic integrator SABA1064 of Farrés et al (2013), using a step size of 5×10 −3 yr and general relativity corrections. The fundamental frequencies of the systems are the mean motions n b and n c , and the two secular frequencies of the pericenters g 1 and g 2 (Table 6).…”
Section: Secular Couplingmentioning
confidence: 99%
“…The coefficients of these methods can be optimized according to many criteria, for example to reduce the coefficients associated to certain types of elementary differentials appearing in the leading error term [260], or to have maximal performance for particular families of applications, such as celestial mechanics [37,127]. For many applications, for example celestial mechanics, such high order methods, and improved variants, are extremely useful, but in the setting of molecular dynamics, it is often found that second-order methods provide a 'good enough' option for numerical integration, the computational price-tag of higher order methods outweighing potential numerical gains.…”
Section: Higher Order Symplectic Methods: the Suzuki-yoshida Methodsmentioning
confidence: 99%
“…Long-term simulations of the stability of the solar system [40,29] (18-digit and 31-digit arithmetic).…”
Section: Computations That Require Extra Precisionmentioning
confidence: 99%